Case for hospital nurse-to-patient ratio legislation in Queensland, Australia, hospitals: an observational study. Issue 9 (6th September 2020) - McHugh, Matthew D; Aiken, Linda H; Windsor, Carol; Douglas, Clint; Yates, Patsy
Abstract : Objectives: To determine whether there was variation in nurse staffing across hospitals in Queensland prior to implementation of nurse-to-patient ratio legislation targeting medical-surgical wards, and if so, the extent to which nurse staffing variation was associated with poor outcomes for patients and nurses. Design: Analysis of cross-sectional data derived from nurse surveys linked with admitted patient outcomes data. Setting: Public hospitals in Queensland. Participants: 4372 medical-surgical nurses and 146 456 patients in 68 public hospitals. Main outcome measures: 30-day mortality, quality and safety indicators, nurse outcomes including emotional exhaustion and job dissatisfaction. Results: Medical-surgical nurse-to-patient ratios before implementation of ratio legislation varied significantly across hospitals (mean 5.52 patients per nurse; SD=2.03). After accounting for patient characteristics and hospital size, each additional patient per nurse was associated with 12% higher odds of 30-day mortality (OR=1.12; 95% CI 1.01 to 1.26). Each additional patient per nurse was associated with poorer outcomes for nurses including 15% higher odds of emotional exhaustion (OR=1.15; 95% CI 1.07 to 1.23) and 14% higher odds of job dissatisfaction (OR=1.14; 95% CI 1.02 to 1.28), as well as higher odds of concerns about quality of care (OR=1.12; 95% CI 1.01 to 1.25) and patient safety (OR=1.32; 95% CI 1.11 to 1.57). Conclusions: Before ratios were implemented, nurse staffing varied considerably across Queensland hospital medical-surgical wards and higher nurse workloads were associated with patient mortality, low quality of care, nurse emotional exhaustion and job dissatisfaction. The considerable variation across hospitals and the link with outcomes suggests that taking action to improve staffing levels was prudent.